A new surgical method for the treatment of pilonidal coccyx cyst (clinical case) - R. A. Pakhomova; K. V. Klimenko; L. V. Kochetova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Relevance. The pilonidal cyst of the coccyx is a narrow channel lined with epithelium containing hair follicles, sebaceous glands, which opens on the skin of the interdigital fold more often with one or more punctate openings. The question of the etiology and pathogenesis of the disease is still controversial. The development of methods of surgical treatment of this disease began in the middle of the XIX century, during which time a huge number of options for interventions were proposed, but to date there is no single approach to the surgical treatment of pilonidal disease.The aim of the study was to evaluate the results of treatment of pilonidal coccyx cyst with a new surgical method.Material and methods. The article describes the author's method of surgical treatment of a pilonidal cyst, protected by patent RU 2,760,094. Early and longterm treatment results are presented.Results. When using a new method of surgical treatment of pilonidal coccyx cyst, the time of wound epithelialization, inpatient bed-day and time of disability of patients decrease, the percentage of postoperative complications decreases, the cosmetic result of surgery and the quality of life of patients significantly improve.Conclusions. A new surgical method for the treatment of pilonidal coccyx cyst improves the quality of life and reduces the risk of recurrence.